Television and the ama: The continuing search for a real Japan in NHK's morning drama Amachan. Issue 2 (1st August 2019) - Martinez, Dolores P.
This article analyses NHK's 2013 hit morning drama (asadora) Amachan, exploring the subject of surviving through adversity as not just a common thread that it shares with almost all the asadora produced since 1961 but also as a theme analogous to the story of post-war Japan. Intimacy and connectivity, as well, are seen as key to understanding this series about a young girl learning to be a diver (ama). I argue that these strands are interwoven to depict a post-bubble and post-3/11 Japan in which a positive attitude and a willingness to learn from rural, traditional, values are seen as leading to happiness and success.